1985
DOI: 10.3109/00498258509045335
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of hydroxylated maprotiline metabolites

Abstract: Lipophilic maprotiline metabolites were extracted from human urine and animal excreta, with or without prior enzymic hydrolysis, purified by repeated t.l.c. and their structures determined by u.v., n.m.r. and mass spectrometry. Urine from patients under treatment with maprotiline contained the isomeric phenols, 2- and 3-hydroxymaprotiline, the 2,3-dihydrodiol, and an alcoholic metabolite, besides smaller quantities of the corresponding N-demethylated compounds. In dog urine and/or faeces the same products of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…To our knowledge, this is the first report demonstrating that maprotiline biotransformation co-segregates with that of debrisoquine. The major metabolites in urine are 3-hydroxymaprotiline and 3-hydroxydesmethylmaprotiline [14]. Our findings are in contrast to those of an earlier study [15] which concluded that PM of debrisoquine do not have higher plasma maprotiline concentrations than EM.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, this is the first report demonstrating that maprotiline biotransformation co-segregates with that of debrisoquine. The major metabolites in urine are 3-hydroxymaprotiline and 3-hydroxydesmethylmaprotiline [14]. Our findings are in contrast to those of an earlier study [15] which concluded that PM of debrisoquine do not have higher plasma maprotiline concentrations than EM.…”
Section: Discussioncontrasting
confidence: 99%
“…Maprotiline is metabolized to desmethylmaprotiline (active) mainly (ϳ80% in EMs) by CYP2D6 (Brachtendorf et al, 2003). Other metabolites (e.g., hydroxy derivatives) (Breyer-Pfaff et al, 1985) may also be active. The AUC of maprotiline (metabolites not measured) was 3.5-fold higher in PMs than in EMs after 50 mg twice daily for 8 days, and the half-life was proportionately longer.…”
Section: Doxepin (Tertiary)/desmethyldoxepin (Secondary)mentioning
confidence: 99%
“…1. Maprotiline and its major metabolites (Riess et al 1975;Breyer-Pfaff et al 1985, the maprotiline metabolic ratio in this patient was still higher than expected for poor metabolisers of CYP2D6. There was no duplication of the CYP2D6*2A allele seen in genotyping, and ultra-rapid metabolism via a highly active CYP1A2 was precluded in this patient as well.…”
mentioning
confidence: 61%
“…In summary, the inhibition data set suggests that CYP2D6 is the high affinity and CYP1A2 is the low affinity binding site, respectively, for maprotiline N‐demethylation. For a substrate concentration of 1 μM (278 ng/ml), which corresponds to typical maprotiline plasma concentrations (Riess et al 1975; Breyer‐Pfaff et al 1985), CYP2D6 would be responsible for 83% and CYP1A2 for 17% of overall maprotiline N‐demethylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation